A single donor cassette enables site-specific knock-in at either the αAmy3 or αAmy8 locus in rice cells via CRISPR/Cas9 - Desyanti Saulina Sinaga; Po-Yu Huang; Chun‑Kai Huang; Chung-An Lu; Li-Fen Huang (Applied Microbiology and Biotechnology)
Abstract CRISPR/Cas9 gene editing is widely used to manipulate gene expression and integrate transgenes into specific target sites, making it a powerful tool for recombinant protein expression. In this study, we generated a single donor cassette for CRISPR/Cas9-mediated knock-in at either the αAmy3 or αAmy8 locus in rice cells. The transgene was inserted downstream of the promoter and first exon of the rice αAmy3 or αAmy8 genes, which are highly expressed under sugar-starved conditions in rice suspension cultures. We constructed a simple vector with the homologous intron sequences of the αAmy3 and αAmy8, along with rice codon-optimized recombinant receptor binding domain (rcRBD) of the SARS-CoV-2 spike protein, a functional domain responsible for binding to the angiotensin-converting enzyme 2 (ACE2) receptor on host cells. Using this construct, rcRBD was successfully integrated into the intron 1 of either the αAmy3 or αAmy8 genes. As a result, rcRBD expression was driven by endogenous αAmy3 or αAmy8 promoter-signal peptide. Under the control of αAmy3-signal peptide, rcRBD proteins was detected in both the soluble cellular protein fraction and culture medium, whereas expression driven by the αAmy8 promoter-signal peptide was exclusively detected in the culture medium of rice suspension cells. The highest secreted protein yield of rcRBD in the rice culture medium under the control of αAmy8 endogenous promoter reached 20.7 mg/L, demonstrating a production efficiency comparable to that driven by the endogenous αAmy3 promoter.